Pengolahan Keripik Biji Durian sebagai strategi berkelanjutan untuk mengurangi limbah dan mendorong ekonomi lokal Desa Kebondowo - Eldina, Septian Najmul; Purwaningsih, Rana Aziyah; Afifah, Hasna Unia; Sholikhah, Mar’atus; Arinta, Yusvita Nena (Tintamas: Jurnal Pengabdian Indonesia Emas, 2024)
Kebondowo Village, Banyubiru District, Semarang Regency, is known for its natural resource of durian. Until now, the people of Kebondowo Village have only sold durians without processing them further. During durian season, durian seed waste is abundant but remains unused by the community despite durian seeds containing nutritional value and health benefits. Therefore, an initiative to process durian seeds into chips is necessary, as it not only addresses the issue of waste but also helps stimulate the local economy. This community service project was carried out through preparation, production, and training. The outcome of this activity was the successful processing of durian seed waste into a valuable economic product. Durian seed chips can be sold as a snack with high demand in the market. Consequently, processing durian seeds into chips provides a business opportunity and additional income for local farmers or community members involved in the production process. This initiative is expected to equip the community, especially housewives/homemakers, with the knowledge to turn durian seeds into a business opportunity. Furthermore, it is hoped that durian seed chips can become a signature snack of Kebondowo Village, serving as a souvenir and potentially being marketed beyond the local area.